Penerapan Teknik Cognitive Restructuring Dalam Mengatasi Konsep Diri Yang Negatif Pada Waria (Studi Kasus Pada Klien “I” Di Muara Pinang Baru Kec. Muara Pinang Kab. Empat Lawang) - Peri Winata; Suryati suryati; Hartika Utami Fitri (Social Science and Contemporary Issues Journal, 2023)
ABSTRACT: Deviant sexual behavior has been known since ancient times. The Koran mentions sexual deviations committed by his people, one of Prophet Luth was transvestites. The term transvestites is given to people who were born male, but have sexual and psychological tendencies as women. Transvestites are men who have characteristics, attitudes like women, look like women so that their daily lives are like women, but sometimes their male characteristics come out when things are tight. The purpose of this research is to determine the description of the self-concept and daily behavior of client "I" and to find out how to apply Cognitive Restructuring techniques in overcoming negative self-concept in client "I". This research uses a qualitative approach method with the type of case study research and data analysis from Robert K Yin who divides three case study analysis techniques, namely: pattern matching, making explanations, and time series analysis. The data used can be obtained using observation, interviews and documentation methods. The subject in this research is client "I". The informants in this research consisted of the aunt and close friends of client "I". The results of the research obtained an overview of the self-concept and daily behavior of client "I", he felt comfortable and happy when he expressed his satisfaction with being a woman, his daily behavior was to look like a woman by wearing make-up, wearing women's clothes, dressing up like a woman, and waddled like a woman. The application of cognitive restructuring techniques in overcoming the negative self-concept of transvestites, the client "I" has experienced changes, namely that he is willing to know, understand and assess who he really is, he has slowly changed and abandoned his transvestites attributes.